The Mechanical Properties of the Concrete Using Metakaolin Additive and Polymer Admixture - Adel Al Menhosh; Yan Wang; Yu Wang (Journal of Engineering)
Environmentally friendly and high performance concrete is very import for the applications in sewage and water treatment industry. Using mineral additives such as fly ash and silica fume has been proven to be an effective approach to improve concrete properties. This paper reports a study of the effect of using both polymer and metakaolin additives together on the mechanical and durability properties of concrete. Different proportions of the combination using two different polymers, metakaolin, and recycled fiber reinforcement have been studied. The effects of water-to-cement ratio and the curing methods have also been compared. At last an optimized mixture and curing method has been suggested.